Psychosocial risk factors for overuse injuries in competitive athletes: a mixed-studies systematic review - Tranaeus, U.; Martin, S.; Ivarsson, A. (Sports Medicine, 2022)
Background: While the psychosocial risk factors for traumatic injuries have been comprehensively investigated, less is known about psychosocial factors predisposing athletes to overuse injuries. Objective: The aim of this review was to systematically identify studies and synthesise data that examined psychosocial risk factors for overuse injuries in athletes. Design: Systematic review. Data Sources: MEDLINE, Web of Science and PsycINFO databases, supplemented by hand searching of journals and reference lists. Eligibility Criteria for Selecting Studies: Quantitative and qualitative studies involving competitive athletes, published prior to July 2021, and reporting the relationship between psychosocial variables and overuse injury as an outcome were reviewed. This was limited to academic peer-reviewed journals in Swedish, English, German, Spanish and French. An assessment of the risk of bias was performed using modified versions of the RoBANS and SBU Quality Assessment Scale for Qualitative Studies. Results: Nine quantitative and five qualitative studies evaluating 1061 athletes and 27 psychosocial factors were included for review. Intra-personal factors, inter-personal factors and sociocultural factors were found to be related to the risk of overuse injury when synthesised and reported according to a narrative synthesis approach. Importantly, these psychosocial factors, and the potential mechanisms describing how they might contribute to overuse injury development, appeared to be different compared with those already known for traumatic injuries. Conclusions: There is preliminary evidence that overuse injuries are likely to partially result from complex interactions between psychosocial factors. Coaches and supporting staff are encouraged to acknowledge the similarities and differences between traumatic and overuse injury aetiology.